2003
DOI: 10.1128/jcm.41.9.4471-4474.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in katG , inhA , and ahpC Genes of Brazilian Isoniazid-Resistant Isolates of Mycobacterium tuberculosis

Abstract: The presence of mutations in specific regions of the katG, inhA, and ahpC genes was analyzed with 69 Mycobacterium tuberculosis isoniazid-resistant isolates from three Brazilian states. Point mutations in codon 315 of the katG gene were observed in 87.1, 60.9, and 60% of the isolates from Rio Grande do Sul, Rio de Janeiro, and São Paulo, respectively. Mutations in the inhA gene were identified only in one isolate from RJ State, and the ahpC promoter region revealed mutations in distinct positions in 12.9, 21.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 24 publications
8
41
2
2
Order By: Relevance
“…In agreement with our data, others have reported that 64% of 70 isolates from India have this mutation (Nusrath et al 2008), as well as 62% of 79 isolates from Spain (Torres et al 2002) and 53% of 67 isolates from the North of Mexico (Viader-Salvadó et al 2003). In partial agreement, others have found that 67% of 37 isolates from the North of Mexico have this mutation (Ramaswamy et al 2004), as well as 69% of 105 isolates from Poland (Sajduda et al 2004) and 72% of 69 isolates from Brazil (Silva et al 2003). Finally, in another study, no variability was observed in the mutation frequency of codon 315; a mutation was observed in 100% of 92 isolates from Kazahastan, Belarus (Hilleman et al 2005).…”
Section: Resultssupporting
confidence: 82%
“…In agreement with our data, others have reported that 64% of 70 isolates from India have this mutation (Nusrath et al 2008), as well as 62% of 79 isolates from Spain (Torres et al 2002) and 53% of 67 isolates from the North of Mexico (Viader-Salvadó et al 2003). In partial agreement, others have found that 67% of 37 isolates from the North of Mexico have this mutation (Ramaswamy et al 2004), as well as 69% of 105 isolates from Poland (Sajduda et al 2004) and 72% of 69 isolates from Brazil (Silva et al 2003). Finally, in another study, no variability was observed in the mutation frequency of codon 315; a mutation was observed in 100% of 92 isolates from Kazahastan, Belarus (Hilleman et al 2005).…”
Section: Resultssupporting
confidence: 82%
“…The MIC values for these two INH-resistant strains were reported to be ≥ 16 mg mL -1 . 25 As the IQG607 compound needs no KatG activation and is effective against INH-resistant strains harboring structural gene and promoter region mutations, this compound appears to be a promising candidate to treat a large proportion of patients infected with INHresistant M. tuberculosis strains. However, it should be pointed out that the mechanism of action of INH is complex, as mutations in at least five different genes (katG, inhA, ahpC, kasA, and ndh) have been found to correlate with INH resistance.…”
Section: Iqg607 Susceptibility Testsmentioning
confidence: 99%
“…INH and IQG607 growth inhibition activity was tested against the wild-type, INH-sensitive M. tuberculosis H37Rv (ATCC 27294) strain and two INH-resistant clinical isolates of M. tuberculosis, harboring mutations in the inhA structural (S94A) or in the inhA regulatory region [C(-15)T]. 25 The mycobacterial strains were cultivated in Middlebrook 7H9 (Difco) liquid medium supplemented with 10% (v/v) OADC (oleic acid, albumin, dextrose, catalase; Becton Dickinson) and 0.05% (m/v) Tween 80 (Sigma). Cultures were initially grown at 37 °C up to an optical density of ca.…”
Section: Mic Values For Inh (Control Drug) and Iqg607 (Test)mentioning
confidence: 99%
See 1 more Smart Citation
“…Neste estudo todas as cepas com resistência à H tiveram suas mutações identificadas nos genes KatG e inhA, com 27,8% e 72,3%, respectivamente. A mutação S315T1 foi a mutação mais frequente associada ao gene KatG concordando com estudos nacionais e internacionais (Silva et al, 2003Seifert et al, 2015. A mutação em inhA estava relacionada com mutações no códon 15 sendo esta mutação associada a cepas monorresistentes (Liu et al, 2015) Os resultados fenotípicos e genotípicos encontrados neste trabalho concordam com estudos nacionais e internacionais que apontam a vantagem decorrente da significativa redução do tempo para o diagnóstico da TB (Chikamatsu et al, 2011;Asencios et al, 2012;Perizzolo et al, 2012;Nosova et al, 2013).…”
Section: Transferências Os Indicadores Distritais Se Aproximam Daqueunclassified